Pembentukan Karakter Positif Peserta Didik Melalui Pendekatan Psikologi Islam - Millah, Maulida Ni’matul; Shanie, Arshan; Pramesti, Neila Sari; Agustin, Riska Maidita; Asyifaurrohmah, Niken Ayu; Ibrahim, Faza Prisma (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Strengthening positive character among primary school students, especially in lower grades, is a crucial priority in education to shape morally responsible individuals from an early age. This study aims to explore the application of Islamic psychology in character building among third-grade students at MI Nahdlotut Tholibin Demak. A qualitative method with a case study design was employed. The study involved 30 third-grade students and classroom teachers as key informants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that regular worship routines, teacher role modeling, and reflective practices based on Islamic values effectively nurture traits such as honesty, discipline, responsibility, and empathy. Teachers play a vital role in instilling these values through a holistic and contextual approach. The study recommends intensive training for teachers in applying Islamic psychological principles in classroom settings, along with institutional support to foster a school environment conducive to comprehensive character development.